Effect of altered gluteus maximus strength on the magnitude and direction of hip joint contact forces during simulations of gait. - Jay R Patel; Madeline Grosklos; Cara L Lewis; Stephanie Di Stasi (PLoS ONE)
Femoroacetabular Impingement Syndrome (FAIS), a common and painful hip condition that affects active young adults, is associated with muscle weakness and altered movement patterns during common daily activities. FAIS is believed to be a precursor to osteoarthritis through disrupted loading patterns; thus, understanding how weakness affects joint loading may provide insights into the pathogenesis from FAIS to osteoarthritis. The aim of this study was to examine the impact of gluteus maximus strength on hip joint contact forces during gait using musculoskeletal modeling. Twelve individuals with FAIS and 13 healthy controls were included in the study and five conditions of gluteus maximus strength (50%, 75%, 100%, 125%, and 150% of the model's default strength) were examined. Differences in the magnitude of the resultant joint contact force and directional components of the joint contact force between groups (FAIS vs controls) and between strength conditions were assessed with statistical nonparametric mapping. Joint contact forces were also used to determine the direction of hip loading in the sagittal and frontal planes and the center of the loading area was compared between groups and between strength conditions using independent t-tests and repeated measures analysis of variance, respectively. Joint contact force magnitude and direction did not differ between FAIS and control groups, aside from a brief period of larger medial force in the FAIS group. With both groups combined for remaining analyses, magnitude and direction of the joint contact force changed with the varied strength conditions; specifically, the 50 and 75% strength conditions demonstrated a lower magnitude joint contact force with a more anterior and medial direction. Importantly, these changes were small and of questionable clinical value. Future investigations should model movement changes alongside strength changes and use magnetic resonance imaging to examine a mechanistic link between load and intraarticular joint health.